THE EFFECT OF THE QUANTUM TEACHING MODEL ON THE SCIENCE PROCESS SKILLS OF CLASS V ELEMENTARY SCHOOL STUDENTS - Meisari, Dwi Pratiwi; Kune, Syarifuddin; Bancong, Hartono (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
This research is a quasi-experimental study with the form of nonequivalent control group design which was conducted to determine the effect of the quantum teaching learning model on the science process skills of fifth grade elementary school students with the concept of heat transfer. The number of samples was 34, with the experimental class applying the quantum teaching model namely fifth grade students at SDN 216 Dualimpoe 17 people, and the control class applying direct learning coming from fifth grade students at SDN 54 Dualimpoe totaling 17 people. The results of the descriptive analysis of experimental class students obtained an average KPS posttest score of 68.12 with an n-gain score of 0.54 in the medium category. While the control class got an average KPS posttest of 48.29 and an n-gain score of 0.21 in the low category. For the results of inferential analysis after passing the prerequisite test, the hypothesis test using the t-test obtained a sig value. is 0.000 <0.05 and the t value is 15.802> 2.1199 t table so it can be concluded that there is an effect of the quantum teaching model on science process skills for elementary school students on the concept of heat transfer